Enhanced design methodology of a low power stall regulated wind turbine. BEMT and MRF-RANS combination and comparison with existing designs. Issue 190 (July 2019) - Torregrosa, A.J.; Gil, A.; Quintero, P.; Tiseira, A.
Abstract: Wind energy importance has increased over the past decades. Energy generation by small turbines installed near urban locations has experienced noticeable growth. This work is focused on the development of a design methodology for a low power blade well suited for all the wind operation conditions. First, a complete Design of Experiments will be presented using the low computational cost tool Blade Element Momentum Theory (BEMT) in order to discard those designs which are clearly not suited to the requirements of the system. Later, the remaining were analyzed using a Computational Fluid Dynamics (CFD) methodology in order to account for three dimensional effects. The value of the left slope of the non-dimensional power curve has been found to be a key parameter for the design. This methodology has been validated with experimental results available from NREL Phase VI wind turbine, allowing to conclude that BEMT is capable to provide with pre-design accurate results which, nevertheless, should corrected by CFD. The results of the proposed design are analyzed and compared to the CFD predictions of a commercial existing blade designed to comply with similar working. For the proposed design, predictions indicate better behavior in terms of maximum power and controllability.